Overexpression of NPR1 in Brassica juncea Confers Broad Spectrum Resistance to Fungal Pathogens - Ali, Sajad; Mir, Zahoor A.; Tyagi, Anshika; Mehari, Hailay; Meena, Rajendra P.; Bhat, Javaid A.; Yadav, Prashant; Papalou, Pradeep; Rawat, Sandhya; Grover, Anita (Frontiers in Plant Science, 2017)
Brassica juncea (Indian mustard) is a commercially important oil seed crop, which is highly affected by many biotic stresses. Among them, Alternaria leaf blight and powdery mildew are the most devastating diseases leading to huge yield losses in B. juncea around the world. In this regard, genetic engineering is a promising tool that may possibly allow us to enhance the B. juncea disease resistance against these pathogens. NPR1 (non-expressor of pathogen related gene 1) is a bonafide receptor of salicylic acid (SA) which modulates multiple immune responses in plants especially activation of induced and systemic acquired resistance (SAR). Here, we report the isolation and characterization of new NPR1 homolog (BjNPR1) from B. juncea. The phylogenetic tree constructed based on the deduced sequence of BjNPR1 with homologs from other species revealed that BjNPR1 grouped together with other known NPR1 proteins of Cruciferae family, and was nearest to B. napus. Furthermore, expression analysis showed that BjNPR1 was upregulated after SA treatment and fungal infection but not by jasmonic acid (JA) or abscisic acid (ABA). To understand the defensive role of this gene, we generated B. juncea transgenic lines overexpressing BjNPR1, and further confirmed by PCR and southern blotting. The transgenic lines showed no phenotypic abnormalities, and constitutive expression of BjNPR1 activates defense signaling pathways by priming the expression of antifungal PR genes. Moreover, BjNPR1 transgenic lines showed enhanced resistance to Alternaria brassicae and Erysiphe cruciferarum as there was delay in symptoms and reduced disease severity than non transgenic plants. In addition, the rate of disease spreading to uninfected or distal parts was also delayed in transgenic plants thus suggesting the activation of SAR. Altogether, the present study suggests that BjNPR1 is involved in broad spectrum of disease resistance against fungal pathogens.